2011
DOI: 10.1007/s11274-011-0653-2
|View full text |Cite
|
Sign up to set email alerts
|

Bioaugmentation with a novel alkali-tolerant Pseudomonas strain for alkaline phenol wastewater treatment in sequencing batch reactor

Abstract: A novel alkali-tolerant strain JY-2, which could utilize phenol as sole source of carbon and energy, was isolated from activated sludge. It was identified as Pseudomonas sp. by 16S rDNA sequencing analysis. The appropriate conditions for strain growth and phenol biodegradation were as follows: pH 8.0-10.0 and temperature 23-30°C. With initial phenol concentrations of 225, 400, 550 and 750 mg/l, the degradation efficiencies were 94.9, 93.3, 89.3 and 48.2% within 40 h at pH 10.0 and 30°C, respectively. The alkal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…As with nitrogen, bioaugmentation has been demonstrated to have some success in the treatment of such compounds. Qu et al (2011) observed improved long-term stability of treatment systems for treating aromatic compounds.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…As with nitrogen, bioaugmentation has been demonstrated to have some success in the treatment of such compounds. Qu et al (2011) observed improved long-term stability of treatment systems for treating aromatic compounds.…”
Section: Discussionmentioning
confidence: 94%
“…Applications may include the use of a single strain or a combination of strains to produce a suitable consortium (Khehra et al, 2005;Qu et al, 2011). An individual strain may be selected for its ability to degrade a specific compound or due its role in a more complex degradation pathway.…”
Section: Strain Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…pH could significantly influence the physiology of microbes, such as optimal of enzyme activities, which finally influence the efficiency of biological treatment process [28]. In our previous study, it also showed that pH is beneficial to strain HF-1 colonization [18].…”
Section: Effect Of Initial Ph On the Set-up Of Bioaugmented Sbrsmentioning
confidence: 87%
“…The Fig (8) showed that Bacillus badius D1 was actively involved in biodegradation process inducing biotransformation enzymes [41]. It is well reputed that effect of particular concentration, temperature, pH, carbon and nitrogen affect significantly on biodegradation [42][43][44][45]. The biotransformation enzyme induction was reported in case of ‫ﻻ‬ Proteobacterium and others [46][47][48][49].…”
Section: Discussionmentioning
confidence: 99%